Polymorphism in the interferon-alpha gene family. - Golovleva, I. (1996)
A pronounced genetic polymorphism of the interferon type I gene family has been assumed on the basis of RFLP analysis of the genomic region as well as the large number of sequences published compared to the number of loci. However, IFNA2 is the only locus that has been carefully analyzed concerning gene frequency, and only naturally occurring rare alleles have been found. We have extended the studies on a variation of expressed sequences by studying the IFNA1, IFNA2, IFNA10, IFNA13, IFNA14, and IFNA17 genes. Genomic white-blood-cell DNA from a population sample of blood donors and from a family material were screened by single-nucleotide primer extension (allele-specific primer extension) of PCR fragments. Because of sequence similarities, in some cases "nested" PCR was used, and, when applicable, restriction analysis or control sequencing was performed. All individuals carried the interferon-alpha 1 and interferon-alpha 13 variants but not the LeIF D variant. At the IFNA2 and IFNA14 loci only one sequence variant was found, while in the IFNA10 and IFNA17 groups two alleles were detected in each group. The IFNA10 and IFNA17 alleles segregated in families and showed a close fit to the Hardy-Weinberg equilibrium. There was a significant linkage disequilibrium between IFNA10 and IFNA17 alleles. The fact that the extent of genetic polymorphism was lower than expected suggests that a majority of the previously described gene sequences represent nonpolymorphic rare mutants that may have arisen in tumor cell lines.